Foundry sand containing bentonite and preparation method thereof
Through the use of modified sodium-based bentonite and modified graphite, combined with α-starch, the problem of insufficient temperature resistance and adhesion of cast molding sand is solved, the amount of coal powder is reduced, environmental pollution is reduced, and the casting process is improved. Environmental protection and casting quality.
Patent Information
- Application Number
- CN202411472083.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-22
AI Technical Summary
In the prior art, cast molded sand containing bentonite has problems such as insufficient temperature resistance and poor adhesiveness. At the same time, the large amount of coal powder is used to cause serious environmental pollution.
Modified sodium-based bentonite and modified graphite are used to prepare cast molding sand with high temperature resistance, strong adhesion and low coal powder consumption by sodium-modified bentonite and surface etching graphite, combined with α-starch.
The high temperature resistance and adhesion of cast molding sand has been improved, the amount of coal powder is reduced, environmental pollution is reduced, and the environmental protection of the casting process and the quality of casting is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to bentonite-containing foundry sand and a preparation method thereof, belonging to the technical field of metal casting. Background Art
[0002] Grooved pipe connection is the first choice technology for connecting liquid and gas pipelines. After just a few years of development and application, it has gradually replaced the two traditional pipe connection methods of flange and welding. Grooved pipe connection technology is relatively mature and widely recognized by the market. National laws and regulations have also actively guided it. Therefore, its market application scope and development prospects are very broad. Grooved pipe connectors are generally made of ductile iron parts and are produced using traditional clay green sand casting technology.
[0003] Clay green sand is a green sand with bentonite as a binder. Its basic characteristics are: it has a certain wet strength, good yield, easy to drop sand, more than 90% of the old sand can be reused, low material cost, high molding efficiency, short production cycle, easy to organize flow production, and easy to realize the mechanization and automation of the production process. However, when clay green sand is used to cast ductile iron parts, because ductile iron solidifies in a "paste solidification mode", there is a process of graphitization expansion during the eutectic transformation, which forces the mold wall to move toward the direction of the water condensation layer, affecting the dimensional accuracy of the casting. After the surface of the mold expands, the "shrinkage after expansion" will also expand the internal shrinkage cavities, shrinkage and other defects, affecting the intrinsic quality of the casting. Therefore, ductile iron parts have higher requirements for the quality and performance of clay green sand. Clay green sand is mainly composed of old sand, raw sand, bentonite and additives (coal powder, α-starch) and other components. Among them, bentonite and additives have a vital influence on the casting process and are the key factors determining the quality of castings.
[0004] During the casting process, bentonite has the characteristics of strong adhesion, high plasticity, good demoulding, excellent air permeability, and stable physical and chemical properties under high temperature and wet conditions. It can prevent sand inclusion, scarring, block falling, sand mold collapse, etc. in castings. It is also convenient to clean sand from castings and has stronger heat resistance. As long as the heating temperature does not exceed the limit (the general failure temperature of sodium-based bentonite is 638°C, that of calcium-based bentonite is 316°C, and the aging temperature of artificially activated calcium-based bentonite is different due to different activation conditions, but they are all lower than sodium-based bentonite), the bentonite that has been free of free water can restore its bonding ability by adding water. Under the influence of the temperature of the molten iron during casting, only a small amount of bentonite in the local high temperature area removes the bound water, loses its bonding ability and becomes dead soil. Because the molding sand has a certain demand for dead soil that loses its bonding effect to ensure the smoothness of the casting surface, there is a certain tolerance range for the upper limit of its stock in the molding sand. Within this range, various indicators such as the strength of the molding sand meet the casting quality requirements, thereby ensuring that the old sand can be recycled many times, reducing the discharge of solid waste. The natural reserves of sodium-based bentonite are small, so the sodium-based bentonite used for casting is mostly obtained by artificial sodium modification of natural calcium-based bentonite. After artificial sodium modification of calcium-based bentonite, sodium-based bentonite with good expansion, adsorption, positive ion exchange, catalytic reactivity, adhesion, floating and ductility can be obtained. However, when it is added to wet molding sand and used as a binder in the foundry industry, its temperature resistance and bonding properties are still difficult to fully meet the high standards of the casting process and the quality of castings.
[0005] The addition of coal powder to clay wet sand plays four main roles in the casting process: (1) After the molten iron is injected into the sand mold, the coal powder in the sand is decomposed by heat. The reducing gas released in the mold cavity can prevent the oxidation of the molten iron and the formation of FeO on the surface of the casting, which is very important for preventing sand sticking defects; (2) After the molten iron fills the mold cavity, the atmosphere inside the mold is a reducing atmosphere. Under this condition, the hydrocarbon gas precipitated by the coal powder will condense on the surface of the mold to form a bright carbon film, which can prevent sand sticking and make the casting clear; (3) Near the metal-mold interface, when the coal powder in the sand is heated and undergoes a coking reaction, it first softens and shrinks in volume, and then expands. The softening temperature of coal powder is roughly the same as the phase change expansion temperature of quartz, which can accommodate the expansion of sand particles. Therefore, it can prevent the occurrence of expansion defects such as sand inclusions and rat tails on the castings, and improve the dimensional stability of the castings; (4) The volume of coal powder expands during coking, which can fill the gaps between the sand particles on the surface of the mold, making it difficult for the molten iron and the fusible silicates produced to penetrate, thereby improving the surface quality of the casting. At the same time, the proper air permeability can still be maintained at a certain distance from the surface of the mold. From the above 4 points, it can be seen that coal powder is an indispensable additive in the clay wet sand formula, but the release of harmful gases due to pyrolysis of coal powder during the casting process will cause a certain degree of pollution. In addition, there is a risk of spontaneous combustion in the storage and transportation of coal powder. Dust pollution during use also has a relatively bad impact on the environment of the foundry workshop. Therefore, seeking substitutes for coal powder or reducing the amount of coal powder used is one of the key concerns of the foundry industry.
[0006] Chinese patent CN107282865A discloses a casting sand for automobile flywheel containing bismuth bentonite, which is made of the following ingredients: quartz sand, water glass, bismuth bentonite, calcium stearate, sodium carboxymethyl cellulose, coal powder, glass fiber, clay, magnesium aluminum silicate, and water; the casting sand for automobile flywheel containing bismuth bentonite provided by the present invention can reduce the pores of automobile flywheel during casting, and the sand inclusion defect is also eliminated, so the sand holes of automobile flywheel are also significantly reduced. The bismuth bentonite prepared by the patent only increases the expansion ratio of bentonite, but the temperature resistance and bonding properties are not improved, so it is difficult to be competent for the casting process with more stringent temperature requirements. In addition, the patent does not pay attention to the reduction or replacement of coal powder, and coal powder pollution is difficult to avoid.
[0007] Chinese patent CN107971452A discloses a green sand for high-density molding of cast iron parts and a preparation method thereof, which is made of the following raw materials in parts by weight: bentonite 0.5-2, mixed soil 0.2-1 (the mixed soil composition is high-efficiency coal powder 70-85, bentonite 10-25, alkalized lignite 2-5, asphalt 3-5, α-starch 2-5), quartz sand new sand 0-5, quartz sand old sand 95-99, water balance. The present invention not only has high wet compressive strength and hot wet tensile strength, but also has excellent air permeability, fluidity and surface dryness, and the molding sand preparation process of the present invention is simple, the manufacturing cost is low, and it is suitable for large-scale promotion and application in high-density molding. The mixed soil used in the patent contains a large amount of coal powder and asphalt, which will seriously increase the environmental pollution of the casting process. Although the wet compressive strength and hot wet tensile strength of the green sand are improved, it does not conform to the development trend of green environmental protection in the foundry industry.
[0008] From the above, we can see that foundry sand containing bentonite still has problems such as insufficient temperature resistance and poor adhesion, large amount of coal powder used and heavy pollution. Therefore, it is of great practical value to develop a formula containing high temperature resistance and high adhesion bentonite and low coal powder content in foundry sand. Summary of the invention
[0009] In view of the deficiencies in the above-mentioned prior art, the present invention provides a bentonite-containing foundry sand and a preparation method thereof, so as to achieve the following invention objectives: to prepare high-quality bentonite-containing foundry sand with good high temperature resistance, high adhesion and low coal powder consumption.
[0010] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0011] A bentonite-containing foundry sand and a preparation method thereof, wherein the bentonite-containing foundry sand specifically comprises: 90-95wt% of old sand, 1-3wt% of raw sand, 0.8-1.7wt% of modified sodium-based bentonite, 0.3-0.8wt% of coal powder, 0.4-1wt% of modified graphite, 0.5-1wt% of α-starch, and the rest less than 100wt% is water;
[0012] The main performance indicators of the used sand are: moisture content 1.4~2.1wt%, mud content 9~11wt%, effective bentonite 7~8wt%, burning mass loss rate 3~4wt%;
[0013] The modified sodium bentonite has the following main performance indicators: no impurities or compaction in appearance, blue absorption of ≥35g per 100g of modified sodium bentonite, wet compressive strength ≥90kPa, water content ≤12wt%, and mass proportion of particles exceeding 75μm sample sieve ≥90wt%;
[0014] The raw sand has the following performance indicators: yellow, uniform particle size and no compaction zone, particle size passing 70 / 140 sieve ≥85wt%, passing 50 / 140 sieve ≥90wt%, mud content ≤0.2wt%;
[0015] The performance indicators of the coal powder are: volatile matter ≥30wt%, ash content ≤7wt%, moisture ≤4wt%, mass proportion of particles with a particle size of 140 mesh or more ≥95wt%, and coke slag characteristics of level 4 to 6;
[0016] The bentonite-containing foundry sand comprises three steps of preparing modified sodium-based bentonite, preparing modified graphite and preparing foundry sand.
[0017] The following are further improvements to the above technical solution:
[0018] Step 1: Preparation of modified sodium bentonite
[0019] The calcium-based bentonite is crushed into a powder of 100-300 meshes, mixed with sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water to form a paste, and then added into an extruder to extrude into strips, and cyclically extruded for 3-5 times, and then put into an oven, dried at 85-100° C. to a moisture content of 4-7wt%, and then ground into a powder of 200-400 meshes after cooling to room temperature to obtain sodium-based bentonite; then, sodium-based bentonite, zirconium carbonate, ammonium carbonate and water are added into a reactor, and stirred and mixed for 2-4.5 hours at a stirring rate of 500-900 rpm, and then the temperature is raised and kept constant at 60-75° C., and then stirred and reacted at a constant temperature for 4-7 hours, and then cooled to room temperature, and then the temperature is lowered to room temperature, and the upper clear liquid is removed, and the lower mud is flattened and dried naturally, and then put into an oven, and dried at 95-115° C. for 15-22 hours to obtain modified sodium-based bentonite;
[0020] The mass ratio of the calcium-based bentonite, sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water is 100-160:10-25:3-8:0.5-1.5:50-90;
[0021] The mass ratio of the sodium bentonite, zirconium carbonate, ammonium carbonate and water is 80-130:5-9:6-12:70-150.
[0022] Step 2: Preparation of modified graphite
[0023] Add graphite and mixed acid solution into a reactor, control the stirring rate at 400-800 rpm, raise the temperature and keep the temperature constant at 70-90°C, stir and react for 2-5 hours, cool to room temperature, filter, wash the filtered solid with water until the washing liquid is neutral, put it into an oven, dry it at 90-120°C for 5-10 hours, and then cool it to room temperature to obtain surface-etched graphite, then put the surface-etched graphite, anhydrous ethanol, and γ-aminopropyltriethoxysilane into a reactor, control the stirring rate at 500-850 rpm, raise the temperature and keep the temperature constant at 60-85°C, stir and react for 5-9 hours under constant temperature condensation reflux, cool to room temperature, filter, wash the filtrate with deionized water for 3-5 times, put it into an oven at 80-95°C, and dry it for 7-10 hours to obtain modified graphite;
[0024] The graphite is one of expanded graphite and microcrystalline graphite;
[0025] The particle size of the graphite is 100-400 mesh;
[0026] The mixed acid solution is composed of nitric acid, trifluoroacetic acid and deionized water, and the mass ratio of the three is 10-40:25-50:100-200;
[0027] The mass ratio of the surface-etched graphite, anhydrous ethanol and gamma-aminopropyltriethoxysilane is 30-70:130-210:5-11.
[0028] Step 3: Preparation of foundry sand
[0029] According to the specific composition of the foundry sand containing bentonite, weigh the old sand, original sand, water, modified sodium bentonite, coal powder, modified graphite and α-starch in advance, first add the old sand, original sand and water into the sand mixer for premixing, the time is controlled within 15 to 30 seconds, and then add the modified sodium bentonite, coal powder, modified graphite and α-starch for comprehensive mixing, the mixing time is controlled within 45 to 90 seconds, after reaching the predetermined mixing time, stop the machine to take out the sand, check the compaction rate of the sand, hold it in your hands to shape it, and it is ok as long as it does not feel wet. If the humidity is not enough and the compaction rate is insufficient, add water for the second time, mix it for 20 to 40 seconds, then take out the sand to check the compaction rate, and after meeting the standard, discharge the material to obtain the foundry sand.
[0030] Compared with the prior art, the present invention achieves the following beneficial effects:
[0031] 1. The present invention uses sodium carbonate as the main sodium agent, and sodium aluminate and water-soluble silicon phosphate are used to sodiumize the calcium-based bentonite. The sodium ions ionized from sodium aluminate and sodium carbonate have the same effect, and penetrate into the ion lattice of the calcium-based bentonite to undergo ion exchange reaction with calcium ions, replacing calcium ions with sodium ions. The aluminate ions ionized from sodium aluminate are much weaker in acidity than carbonate ions, and thus are more likely to undergo weak acid hydrolysis reaction, thereby increasing the The pH value of the sodiumization reaction system is increased, and the rate and thoroughness of the sodiumization reaction are promoted. The aluminate ion itself has a large ion radius. After entering the interlayer structure of calcium-based bentonite, it can effectively expand the distance between the calcium-based bentonite crystal layers, promote the entry of sodium ions and the outflow of calcium ions. The main function of water-soluble silicon phosphate is to quickly complex the free calcium ions in the reaction system, reduce the concentration of calcium ions in the sodiumization reaction system, and further promote the rate and thoroughness of the sodiumization reaction.
[0032] 2. After preparing sodium bentonite, the present invention further modifies the sodium bentonite with zirconium carbonate and ammonium carbonate, wherein the role of ammonium carbonate is to increase the solubility of zirconium carbonate in the modified system. The zirconium ions ionized by the completely dissolved zirconium carbonate can attract hydroxide ions in the water through the action of positive and negative charges, enter between the sodium bentonite crystal layers, and form hydroxy zirconium composite ions, which have a pillaring effect on the crystal layers of the sodium bentonite and cause the expansion of the distance between the sodium bentonite crystal layers, which will enhance the wet expansion effect of the sodium bentonite and enhance the wet strength of the molding sand. At the same time, the thermal stability of the hydroxy zirconium composite ions is relatively good, and the hot wet tensile strength of the molding sand can also be effectively improved;
[0033] 3. The present invention uses mixed acid to slightly etch the graphite surface. After the etching, the surface hydroxyl content of the graphite increases and the polarity increases. After the reaction with γ-aminopropyltriethoxysilane, the graphite surface is rich in γ-aminopropyl. The polarity of γ-aminopropyl is high, and the graphite is easily dispersed more evenly in the aqueous system. Therefore, the modified graphite can be very evenly dispersed in the molding sand, and then can effectively replace part of the coal powder. In the casting process, it cooperates with the coal powder to form a bright carbon layer, thereby reducing the amount of coal powder, reducing environmental pollution, and does not cause any negative impact on the casting process and casting quality;
[0034] 4. The bentonite-containing foundry sand obtained by the present invention has a compaction rate of 36-42%, an air permeability of 90-140, a wet compressive strength of 140-170 kPa, a hot wet tensile strength of 35-39 kPa, a smoke emission of 678-692 mg per kilogram of sand during the entire pouring and cooling process, and a casting roughness of 25. DETAILED DESCRIPTION
[0035] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0036] Example 1: A method for preparing bentonite-containing foundry sand
[0037] Step 1: Preparation of modified sodium bentonite
[0038] The calcium-based bentonite is crushed into a powder of 250 mesh, mixed with sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water to form a paste, and then added into an extruder to extrude into strips, and cyclically extruded for 4 times, and then placed in an oven, dried at 95° C. to a moisture content of 5wt%, and then ground into a powder of 350 mesh after cooling to room temperature to obtain sodium-based bentonite. Then, sodium-based bentonite, zirconium carbonate, ammonium carbonate and water are added into a reactor, and the stirring rate is controlled at 600 rpm, and the mixture is stirred and mixed for 4 hours, and then the temperature is raised and kept constant at 70° C., and then the mixture is stirred and reacted at a constant temperature for 5 hours, and then the mixture is cooled to room temperature, and the mixture is allowed to stand for precipitation and aging for 26 hours, and then the upper clear liquid is removed, and the lower mud is flattened and naturally dried, and then placed in an oven, and dried at 110° C. for 20 hours to obtain modified sodium-based bentonite;
[0039] The mass ratio of the calcium-based bentonite, sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water is 140:19:7:1:80;
[0040] The mass ratio of the sodium bentonite, zirconium carbonate, ammonium carbonate and water is 110:8:11:120.
[0041] Step 2: Preparation of modified graphite
[0042] The graphite and the mixed acid solution were added to a reaction kettle, the stirring rate was controlled at 700 rpm, the temperature was raised and kept constant at 85°C, and the mixture was stirred for reaction for 4 hours, then the mixture was cooled to room temperature, the solid was discharged and filtered, the filtered solid was washed with water until the washing liquid was neutral, and then the mixture was put into an oven, and dried at 110°C for 8 hours, and then the mixture was cooled to room temperature to obtain surface-etched graphite. The surface-etched graphite, anhydrous ethanol, and γ-aminopropyltriethoxysilane were then put into a reaction kettle, the stirring rate was controlled at 750 rpm, the temperature was raised and kept constant at 80°C, and the mixture was stirred for reaction for 8 hours under constant temperature condensation reflux, and then the mixture was cooled to room temperature and filtered. The filtrate was washed with deionized water for 4 times, and then the mixture was put into an oven at 90°C, and dried for 8 hours to obtain modified graphite.
[0043] The graphite is expanded graphite;
[0044] The particle size of the graphite is 300 mesh;
[0045] The mixed acid solution is composed of nitric acid, trifluoroacetic acid and deionized water, and the mass ratio of the three is 30:40:160;
[0046] The mass ratio of the surface-etched graphite, anhydrous ethanol and γ-aminopropyltriethoxysilane is 40:180:9.
[0047] Step 3: Preparation of foundry sand
[0048] According to the specific composition of the foundry sand containing bentonite, weigh the old sand, raw sand, water, modified sodium bentonite, coal powder, modified graphite and α-starch in advance, add the old sand, raw sand and water into the sand mixer for premixing, the time is controlled within 25 seconds, and then add the modified sodium bentonite, coal powder, modified graphite and α-starch for comprehensive mixing, the mixing time is controlled within 80 seconds, after reaching the predetermined mixing time, stop the machine to take the sand, check the compaction rate of the sand, hold it by hand to shape it, and it is OK if it does not feel wet. If the humidity is not enough and the compaction rate is insufficient, add water for the second time, mix it for 35 seconds and then take the sand to check the compaction rate. After reaching the standard, discharge the material to obtain the foundry sand;
[0049] The bentonite-containing foundry sand is specifically composed of: 93wt% of old sand, 2wt% of raw sand, 1wt% of modified sodium-based bentonite, 0.5wt% of coal powder, 0.6wt% of modified graphite, 0.7wt% of α-starch, and the remaining part less than 100wt% is water;
[0050] The main performance indicators of the used sand are: moisture content 1.8wt%, mud content 10wt%, effective bentonite 7.7wt%, and burning mass loss rate 3.6wt%;
[0051] The modified sodium bentonite has the following main performance indicators: no impurities or compaction in appearance, 35 grams of blue absorption per 100 grams of modified sodium bentonite, 90 kPa of wet compressive strength, 12 wt % of water content, and 90 wt % of the mass of the particles exceeding the 75 μm sample sieve;
[0052] The raw sand has the following performance indicators: yellow, uniform particle size and no compaction zone, particle size passing 70 / 140 sieve 85wt%, passing 50 / 140 sieve 90wt%, mud content 0.2wt%;
[0053] The performance indicators of the coal powder are: volatile matter 32wt%, ash content 5wt%, moisture content 3wt%, mass proportion of particles with a particle size of 140 mesh or above 96wt%, and coke slag characteristics level 5.
[0054] Example 2: A method for preparing bentonite-containing foundry sand
[0055] Step 1: Preparation of modified sodium bentonite
[0056] The calcium-based bentonite is crushed into a powder of 100 mesh, mixed with sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water to form a paste, and then added into an extruder to be extruded into strips. After cyclic extrusion for 3 times, the powder is placed in an oven, dried at 85° C. to a moisture content of 4wt%, cooled to room temperature, and then ground into a powder of 200 mesh to obtain sodium-based bentonite. Then, the sodium-based bentonite, zirconium carbonate, ammonium carbonate and water are added into a reactor, and the stirring rate is controlled at 500 rpm, and the mixture is stirred and mixed for 2 hours. The temperature is raised and kept constant at 60° C., and then the mixture is stirred and reacted at a constant temperature for 4 hours, and then the mixture is cooled to room temperature. After being allowed to stand for precipitation and aging for 20 hours, the upper clear liquid is removed, the lower mud is flattened and naturally dried, and then placed in an oven, and dried at 95° C. for 15 hours to obtain modified sodium-based bentonite.
[0057] The mass ratio of the calcium-based bentonite, sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water is 100:10:3:0.5:50;
[0058] The mass ratio of the sodium bentonite, zirconium carbonate, ammonium carbonate and water is 80:5:6:70.
[0059] Step 2: Preparation of modified graphite
[0060] Graphite and mixed acid solution were added to a reaction kettle, the stirring rate was controlled at 400 rpm, the temperature was raised and kept constant at 70°C, and the reaction was stirred for 2 hours, then the temperature was lowered to room temperature, the material was discharged and filtered, the filtered solid was washed with water until the washing liquid was neutral, and then the solid was put into an oven, dried at 90°C for 5 hours, and then the temperature was lowered to room temperature to obtain surface-etched graphite, and then the surface-etched graphite, anhydrous ethanol, and γ-aminopropyltriethoxysilane were put into a reaction kettle, the stirring rate was controlled at 500 rpm, the temperature was raised and kept constant at 60°C, and the reaction was stirred for 5 hours under a constant temperature condensation reflux state, then the temperature was lowered to room temperature, and the solid was filtered, and the filtrate was washed with deionized water for 3 times, and then the solid was put into an oven at 80°C, and then dried for 7 hours to obtain modified graphite;
[0061] The graphite is microcrystalline graphite;
[0062] The particle size of the graphite is 100 mesh;
[0063] The mixed acid solution is composed of nitric acid, trifluoroacetic acid and deionized water, and the mass ratio of the three is 10:25:100;
[0064] The mass ratio of the surface-etched graphite, anhydrous ethanol and γ-aminopropyltriethoxysilane is 30:130:5.
[0065] Step 3: Preparation of foundry sand
[0066] According to the specific composition of the foundry sand containing bentonite, weigh the old sand, raw sand, water, modified sodium bentonite, coal powder, modified graphite and α-starch in advance, add the old sand, raw sand and water into the sand mixer for premixing, the time is controlled within 15 seconds, and then add the modified sodium bentonite, coal powder, modified graphite and α-starch for comprehensive mixing, the mixing time is controlled within 45 seconds, after reaching the predetermined mixing time, stop the machine to take the sand, check the compaction rate of the sand, hold it by hand to shape it, and it is OK if it does not feel wet. If the humidity is not enough and the compaction rate is insufficient, add water for the second time, mix it for 20 seconds and then take the sand to check the compaction rate. After reaching the standard, discharge the material to obtain the foundry sand;
[0067] The bentonite-containing foundry sand is specifically composed of: 90wt% of old sand, 3wt% of raw sand, 1.7wt% of modified sodium-based bentonite, 0.8wt% of coal powder, 1wt% of modified graphite, 1wt% of α-starch, and the remaining part less than 100wt% is water;
[0068] The main performance indicators of the used sand are: moisture content 1.4wt%, mud content 9wt%, effective bentonite 7wt%, and burning mass loss rate 3wt%;
[0069] The modified sodium bentonite has the following main performance indicators: no impurities or compaction in appearance, 36 grams of blue absorption per 100 grams of modified sodium bentonite, 92 kPa of wet compressive strength, 10 wt % of water content, and 93 wt % of the mass of the particles exceeding the 75 μm sample sieve;
[0070] The raw sand has the following performance indicators: yellow, uniform particle size and no compaction zone, particle size passing 70 / 140 sieve 87wt%, passing 50 / 140 sieve 92wt%, mud content 0.1wt%;
[0071] The performance indicators of the coal powder are: volatile matter 30wt%, ash content 7wt%, moisture content 4wt%, mass proportion of particles with a particle size of 140 mesh or above 95wt%, and coke slag characteristics level 4.
[0072] Example 3: A method for preparing bentonite-containing foundry sand
[0073] Step 1: Preparation of modified sodium bentonite
[0074] The calcium-based bentonite is crushed into a powder of 300 mesh, mixed with sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water to form a paste, and then added into an extruder to be extruded into strips. After cyclic extrusion for 5 times, the powder is placed in an oven, dried at 100° C. to a moisture content of 7wt%, cooled to room temperature, and then ground into a powder of 400 mesh to obtain sodium-based bentonite. Then, the sodium-based bentonite, zirconium carbonate, ammonium carbonate and water are added into a reactor, stirred and mixed for 4.5 hours at a stirring rate of 900 rpm, and then the temperature is raised and kept constant at 75° C., and then stirred and reacted at a constant temperature for 7 hours, and then cooled to room temperature, and the supernatant is removed after being allowed to settle and aged for 30 hours, and the upper clear liquid is removed, and the lower mud is flattened and naturally dried, and then placed in an oven, and dried at 115° C. for 22 hours to obtain modified sodium-based bentonite;
[0075] The mass ratio of the calcium-based bentonite, sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water is 160:25:8:1.5:90;
[0076] The mass ratio of the sodium bentonite, zirconium carbonate, ammonium carbonate and water is 130:9:12:150.
[0077] Step 2: Preparation of modified graphite
[0078] The graphite and the mixed acid solution were added to a reaction kettle, the stirring rate was controlled at 800 rpm, the temperature was raised and kept constant at 90°C, and the mixture was stirred for reaction for 5 hours, then the mixture was cooled to room temperature, the solid was discharged and filtered, the filtered solid was washed with water until the washing liquid was neutral, and then the mixture was put into an oven, and dried at 120°C for 10 hours, and then the mixture was cooled to room temperature to obtain surface-etched graphite, and then the surface-etched graphite, anhydrous ethanol, and γ-aminopropyltriethoxysilane were put into a reaction kettle, the stirring rate was controlled at 850 rpm, the temperature was raised and kept constant at 85°C, and the mixture was stirred for reaction for 9 hours under constant temperature condensation reflux, then the mixture was cooled to room temperature, filtered, and the filtrate was washed with deionized water for 5 times, and then the mixture was put into an oven at 95°C, and dried for 10 hours to obtain modified graphite;
[0079] The graphite is microcrystalline graphite;
[0080] The particle size of the graphite is 400 mesh;
[0081] The mixed acid solution is composed of nitric acid, trifluoroacetic acid and deionized water, and the mass ratio of the three is 40:50:200;
[0082] The mass ratio of the surface-etched graphite, anhydrous ethanol and γ-aminopropyltriethoxysilane is 70:210:11.
[0083] Step 3: Preparation of foundry sand
[0084] According to the specific composition of the foundry sand containing bentonite, weigh the old sand, raw sand, water, modified sodium bentonite, coal powder, modified graphite and α-starch in advance, add the old sand, raw sand and water into the sand mixer for premixing, the time is controlled within 30 seconds, and then add the modified sodium bentonite, coal powder, modified graphite and α-starch for comprehensive mixing, the mixing time is controlled within 90 seconds, after reaching the predetermined mixing time, stop the machine to take the sand, check the compaction rate of the sand, hold it by hand to form it, and it is OK if it does not feel wet. If the humidity is not enough and the compaction rate is insufficient, add water for a second time, mix it for another 40 seconds and then take the sand to check the compaction rate. After reaching the standard, discharge the material to obtain the foundry sand;
[0085] The bentonite-containing foundry sand is specifically composed of: 95wt% of old sand, 1wt% of raw sand, 0.8wt% of modified sodium-based bentonite, 0.3wt% of coal powder, 0.4wt% of modified graphite, 0.5wt% of α-starch, and the remaining part less than 100wt% is water;
[0086] The main performance indicators of the used sand are: moisture content 2.1wt%, mud content 11wt%, effective bentonite 8wt%, burning mass loss rate 4wt%;
[0087] The modified sodium bentonite has the following main performance indicators: no impurities or compaction in appearance, 35 grams of blue absorption per 100 grams of modified sodium bentonite, 90 kPa of wet compressive strength, 12 wt % of water content, and 90 wt % of the mass of the particles exceeding the 75 μm sample sieve;
[0088] The raw sand has the following performance indicators: yellow, uniform particle size and no compaction zone, particle size passing 70 / 140 sieve 85wt%, passing 50 / 140 sieve 90wt%, mud content 0.2wt%;
[0089] The performance indicators of the coal powder are: volatile matter 30wt%, ash content 7wt%, moisture content 4wt%, mass proportion of particles with a particle size of 140 mesh or above 95wt%, and coke slag characteristics level 6.
[0090] Comparative Example 1: Based on Example 1, in step 1, in the preparation of modified sodium-based bentonite, sodium aluminate and water-soluble silicon phosphate were not added, and 7 parts of sodium aluminate and 1 part of water-soluble silicon phosphate were replaced by 8 parts of sodium carbonate in equal amounts. The specific operation was as follows:
[0091] Step 1: Preparation of modified sodium bentonite
[0092] Replace 7 parts of sodium aluminate and 1 part of water-soluble silicon phosphate with 8 parts of sodium carbonate in equal amounts, and perform the other operations the same as in Example 1;
[0093] The operations of steps 2 and 3 are the same as those of Example 1.
[0094] Comparative Example 2: Based on Example 1, in step 1, in the preparation of modified sodium bentonite, zirconium carbonate and ammonium carbonate are not added to modify the sodium bentonite. In step 3, in the preparation of foundry sand, 1wt% of the modified bentonite is replaced by 1wt% of sodium bentonite. The specific operation is as follows:
[0095] Step 1, preparation of sodium bentonite
[0096] The calcium-based bentonite is crushed into a powder of 250 mesh, mixed with sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water to form a paste, and then added into an extruder to be extruded into strips, and after cyclic extrusion for 4 times, it is placed in an oven, dried at 95° C. to a moisture content of 5wt%, cooled to room temperature, and then ground into a powder of 350 mesh to obtain sodium-based bentonite, and then the sodium-based bentonite is placed in an oven, and dried at 110° C. for 20 hours to obtain dry sodium-based bentonite;
[0097] The mass ratio of the calcium-based bentonite, sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water is 140:19:7:1:80;
[0098] The operation of step 2 is the same as that of embodiment 1;
[0099] Step 3: Preparation of foundry sand
[0100] According to the specific composition of the foundry sand containing bentonite, the old sand, raw sand, water, sodium bentonite, coal powder, modified graphite and α-starch are weighed in advance, and the old sand, raw sand and water are first added to the sand mixer for premixing, and the time is controlled within 25 seconds, and then the sodium bentonite, coal powder, modified graphite and α-starch are added for comprehensive mixing, and the mixing time is controlled within 80 seconds. After reaching the predetermined mixing time, the machine is stopped to take the sand, and the compaction rate of the sand is checked. The sand is held by hand for molding, and it is OK if it does not feel wet. If the humidity is not enough and the compaction rate is insufficient, water is added for a second time, and the sand is taken out after mixing for 35 seconds to check the compaction rate. After reaching the standard, the foundry sand is obtained by discharging;
[0101] The bentonite-containing foundry sand is specifically composed of: 93wt% old sand, 2wt% raw sand, 1wt% sodium-based bentonite, 0.5wt% coal powder, 0.6wt% modified graphite, 0.7wt% α-starch, and the rest less than 100wt% is water;
[0102] The main performance indicators of the used sand are: moisture content 1.8wt%, mud content 10wt%, effective bentonite 7.7wt%, and burning mass loss rate 3.6wt%;
[0103] The main performance indicators of the sodium bentonite are: no impurities and no compaction in appearance, blue absorption of 35 grams per 100 grams of sodium bentonite, wet compressive strength of 90 kPa, water content of 12 wt%, and the mass of particles passing through a sample sieve with an aperture of 75 μm accounts for 90 wt%;
[0104] The raw sand has the following performance indicators: yellow, uniform particle size and no compaction zone, particle size passing 70 / 140 sieve 85wt%, passing 50 / 140 sieve 90wt%, mud content 0.2wt%;
[0105] The performance indicators of the coal powder are: volatile matter 32wt%, ash content 5wt%, moisture content 3wt%, mass proportion of particles with a particle size of 140 mesh or above 96wt%, and coke slag characteristics level 5.
[0106] Comparative Example 3: Based on Example 1, step 2, preparation of modified graphite, is not performed. In step 3, preparation of foundry sand, 0.6 wt% of modified graphite is replaced by 0.6 wt% of graphite. The specific operation is as follows:
[0107] The operation of step 1 is the same as that of embodiment 1;
[0108] Step 2, preparation of modified graphite is not performed;
[0109] Step 3: Preparation of foundry sand
[0110] The 0.6 wt % modified graphite was replaced by 0.6 wt % graphite in equal amounts, and the other operations were the same as in Example 1.
[0111] Comparative Example 4: Based on Example 1, step 2, preparation of modified graphite, is not performed. In step 3, preparation of foundry sand, modified graphite is not added, and 0.6wt% of modified graphite is replaced by 0.6wt% of coal powder. The specific operation is as follows:
[0112] The operation of step 1 is the same as that of embodiment 1;
[0113] Step 2, preparation of modified graphite is not performed
[0114] Step 3: Preparation of foundry sand
[0115] The 0.6 wt % modified graphite was replaced by 0.6 wt % coal powder, and the other operations were the same as in Example 1.
[0116] Performance Testing:
[0117] The bentonite-containing foundry sand obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, and 4 was tested for compactness, air permeability, wet compressive strength, and hot wet tensile strength with reference to GB / T 2684-2009 Test methods for foundry sand and mixtures. The foundry sand obtained in the above three embodiments and four comparative examples was used to cast ductile iron castings, and the smoke emission per kilogram of the foundry sand during the entire pouring and cooling process was determined. The surface roughness of the ductile iron casting was evaluated with reference to GB / T 15056-2017 Casting Surface Roughness, and the surface roughness was used to evaluate the casting performance of the foundry sand. The specific test results are shown in Table 1:
[0118] Table 1
[0119]
[0120] From the data in Table 1, it can be seen that in the preparation of modified sodium-based bentonite, no sodium aluminate or water-soluble silicon phosphate is added in Comparative Example 1, only sodium carbonate is added. Compared with Example 1, the compaction rate and air permeability of the molding sand in Comparative Example 1 are significantly reduced, the wet compressive strength and hot wet tensile strength decrease more significantly, and the surface roughness of the casting is also greatly reduced, which indicates that without adding sodium aluminate or water-soluble silicon phosphate, the sodium modification effect of calcium-based bentonite is not good, which may be due to the single use of sodium carbonate to replace the calcium-based bentonite. The calcium ions in the bentonite have a limited degree of replacement, which leads to a limited degree of sodiumization of the calcium-based bentonite, thereby affecting the bonding strength, compactness and air permeability of the molding sand dominated by the sodium-based bentonite; in Comparative Example 2, no zirconium carbonate and ammonium carbonate are added to modify the sodium-based bentonite. The compactness, air permeability, wet compressive strength, hot wet tensile strength and casting roughness of Comparative Example 2 are much worse than those of Example 1 and also worse than those of Comparative Example 1, which shows that after zirconium carbonate and ammonium carbonate are used to modify the sodium-based bentonite, the compactness, air permeability, wet compressive strength, hot wet tensile strength and casting roughness of Comparative Example 2 can be significantly improved. The bonding performance and high temperature resistance of high sodium bentonite further improve the two key indicators of compaction rate and hot wet tensile strength of the molding sand; in Comparative Example 3, the graphite is not surface modified, and the compaction rate of Comparative Example 3 is reduced to the lowest value among all embodiments and comparative examples, and the air permeability, wet compressive strength, hot wet tensile strength and casting roughness are also greatly reduced, which shows that the graphite without surface modification is difficult to be dispersed more evenly in the molding sand formula, thereby causing a sharp decline in various properties of the molding sand; in Comparative Example 4, all the modified graphite is replaced with coal powder. Compared with Example 1, the various properties of the molding sand do not change significantly, but the smoke emission during casting and cooling has more than doubled, and Comparative Examples 1, 2, and 3 with less coal powder added are also the same as Example 1, and the smoke emission during casting and cooling is much less than that of Comparative Example 4, which shows that the addition of modified graphite can reduce the amount of coal powder used and reduce the smoke pollution in the casting process, and the modified graphite replaces part of the coal powder without any effect on the casting performance of the molding sand.
[0121] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A foundry sand containing bentonite, characterized in that: The bentonite-containing foundry sand is specifically composed of: 90-95wt% of old sand, 1-3wt% of raw sand, 0.8-1.7wt% of modified sodium-based bentonite, 0.3-0.8wt% of coal powder, 0.4-1wt% of modified graphite, 0.5-1wt% of α-starch, and the rest less than 100wt% is water; The main performance indicators of the used sand are: moisture content 1.4~2.1wt%, mud content 9~11wt%, effective bentonite 7~8wt%, burning mass loss rate 3~4wt%; The modified sodium bentonite has the following main performance indicators: no impurities or compaction in appearance, blue absorption of ≥35g per 100g of modified sodium bentonite, wet compressive strength ≥90kPa, water content ≤12wt%, and mass proportion of particles exceeding 75μm sample sieve ≥90wt%; The raw sand has the following performance indicators: yellow, uniform particle size and no compaction zone, particle size passing 70 / 140 sieve ≥85wt%, passing 50 / 140 sieve ≥90wt%, mud content ≤0.2wt%; The performance indicators of the coal powder are: volatile matter ≥30wt%, ash content ≤7wt%, moisture ≤4wt%, mass proportion of particles with a particle size of 140 mesh or more ≥95wt%, and coke slag characteristics of level 4 to 6; The modified sodium bentonite is prepared by crushing calcium bentonite into powder of 100-300 meshes, mixing and stirring with sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water into a paste, adding the mixture into an extruder and extruding the mixture into strips, circulating the extrusion for 3-5 times, putting the mixture into an oven, drying the mixture at 85-100°C to a moisture content of 4-7wt%, cooling the mixture to room temperature and then grinding the mixture into powder of 200-400 meshes to obtain sodium bentonite, and then mixing the sodium bentonite with the powder. Bentonite, zirconium carbonate, ammonium carbonate and water are added to a reaction kettle, and the stirring rate is controlled at 500-900 rpm. After stirring and mixing for 2-4.5 hours, the temperature is raised and kept constant at 60-75°C, and then stirred and reacted for 4-7 hours at a constant temperature, and then cooled to room temperature. After being allowed to stand for precipitation and aging for 20-30 hours, the upper clear liquid is removed, the lower mud is flattened and naturally dried, and then placed in an oven and dried at 95-115°C for 15-22 hours to obtain modified sodium bentonite; The modified graphite has a preparation method comprising: adding graphite and a mixed acid solution into a reaction kettle, controlling the stirring rate to 400-800 rpm, heating and maintaining the temperature to 70-90°C, stirring and reacting for 2-5 hours, cooling to room temperature, discharging and filtering, washing the filtered solid with water until the washing liquid is neutral, putting it into an oven, drying it at 90-120°C for 5-10 hours, cooling to room temperature to obtain surface-etched graphite, then putting the surface-etched graphite, anhydrous ethanol, and γ-aminopropyltriethoxysilane into a reaction kettle, controlling the stirring rate to 500-850 rpm, heating and maintaining the temperature to 60-85°C, stirring and reacting for 5-9 hours under a constant temperature condensation reflux state, cooling to room temperature, filtering, washing the filtrate with deionized water for 3-5 times, putting it into an oven at 80-95°C, and drying it for 7-10 hours to obtain the modified graphite; The graphite is one of expanded graphite and microcrystalline graphite.
2. The bentonite-containing foundry sand according to claim 1, characterized in that: The mass ratio of the calcium-based bentonite, sodium carbonate, sodium aluminate, water-soluble silicon phosphate and water is 100-160:10-25:3-8:0.5-1.5:50-90; The mass ratio of the sodium bentonite, zirconium carbonate, ammonium carbonate and water is 80-130:5-9:6-12:70-150.
3. The bentonite-containing foundry sand according to claim 1, characterized in that: The particle size of the graphite is 100-400 mesh; The mixed acid solution is composed of nitric acid, trifluoroacetic acid and deionized water, and the mass ratio of the three is 10-40:25-50:100-200; The mass ratio of the surface-etched graphite, anhydrous ethanol and gamma-aminopropyltriethoxysilane is 30-70:130-210:5-11.
4. The method for preparing bentonite-containing foundry sand according to claim 1, characterized in that: The preparation method comprises the following steps: according to the specific composition of the bentonite-containing foundry sand, old sand, raw sand, water, modified sodium bentonite, coal powder, modified graphite and α-starch are weighed in advance; the old sand, raw sand and water are first added into a sand mixer for premixing, and the mixing time is controlled within 15 to 30 seconds; then the modified sodium bentonite, coal powder, modified graphite and α-starch are added for comprehensive mixing, and the mixing time is controlled within 45 to 90 seconds; after reaching the predetermined mixing time, the machine is stopped to take out the sand, and the compaction rate of the sand is checked; the sand is held by hand for molding, and it is OK if it does not feel wet; if the humidity is insufficient and the compaction rate is insufficient, water is replenished for a second time, and the sand is taken out after mixing for 20 to 40 seconds to check the compaction rate; after reaching the standard, the foundry sand is obtained by discharging the material.
Citation Information
Cited By
Foot pad mold based on sand mold 3D printing and preparation method thereof
CN122644522A
